Technological readiness and adoption potential of inventory management software among SMEs in Tacloban City - Cala, Christina Gwyneth L.; Dacuyan, Flordeliz B.; Lanuza, Jhon Goodloe; Mustacisa, Gerchelle L. (Tacloban City Division of Management, University of the Philippines Tacloban, 2024)
This study assesses the technological readiness and adoption potential for inventory management software (IMS) among small and medium-sized enterprises (SMEs) in Tacloban City. Given the critical role of SMEs in job creation and local economic growth, the study explores how IMS can streamline supply chain processes and enhance business operations. Employing a mixed-methods approach, the researchers conducted semi-structured interviews to investigate current inventory management practices, analyzed using Braun and Clarke's Thematic Analysis. A scalar questionnaire based on the Technology Readiness Index (TRI) and Technology Acceptance Model (TAM) was used to evaluate technology readiness and acceptance among SMEs.
The findings reveal that SMEs in Tacloban City display a moderate level of technological readiness and a positive attitude towards IMS adoption, recognizing its potential to improve efficiency and competitiveness despite technological discomfort and insecurity challenges. The study highlights the importance of addressing these barriers through targeted support and training to create a conducive environment for IMS implementation. Consequently, the researchers recommend that SME owners invest in user-friendly inventory management software and provide tailored technology training to enhance efficiency and reduce errors. For future research, adopting a stratified sampling method and exploring additional factors such as industry-specific influences and regional comparisons could offer a more comprehensive understanding of technology readiness and IMS adoption among SMEs.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Information technology -- Management -- Philippines -- Tacloban City; Small and medium-sized enterprises (SMEs) -- Philippines -- Tacloban City; Inventory Management Software (IMS).; Technological readiness; Adoption potential of technology; Business operations; Inventory management practices; Inventory management issues